Decoupling Control of a Disc-type Rotor Magnetic Bearing - Nguyen, Tung Lam (International Journal of Integrated Engineering, 2021)
A disc-type rotor magnetic bearing with 3-pole magnet is considered in the paper. Based on analysing magnetic forces acting on the rotor, a coupling mechanism is identified, and a coordinate transformation is formulated to decouple acting forces. Thanks to the transformation, control design is straightforward for each control channel. The goal of the design is to keep the rotor at its desired equilibrium in the presence of disturbance and parameters variation. To achieve this goal, the controller is designed in discrete-time domain based on the linearized model first. Then, the disturbance is compensated by employing the one step delay technique. The validity and robustness of the controller are verified by various numerical simulations in which both linearized model and original nonlinear model are used.